Land der Häuser: die narrative Inszenierung Ägyptens in der Joseferzählung (Gen 37,39-50) = Land of houses : the narrative construction of Egypt in the Joseph story (Gen 37:39–50) - Feichtinger, Daniela (Protokolle zur Bibel, 2017)
So far, “Egypt” has been subject to biblical research only as setting of the Joseph story. The focus was mainly on the image of Egypt conveyed by the text and the relation of this image to other biblical depictions of Egypt or the historical and geographical entity. Based on the relational theory of space by Martina Löw (Raumsoziologie, 2001), this paper analyses how “Egypt” is narratively constructed as space in Gen 37; 39–50. Central to this construction is the arrangement of houses, which are rather social than architectural entities. Houses constitute Egypt as well as Canaan in specific ways and are also structuring elements of the text.